2019
DOI: 10.1186/s11689-019-9297-6
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Th2 inflammation through neutralizing IL-4 antibody rescues myelination in IUGR rat brain

Abstract: BackgroundIntrauterine growth restriction (IUGR) is a common complication of pregnancy and is associated with significant neurological deficits in infants, including white matter damage. Previous work using an animal model of IUGR has demonstrated that IUGR rats exhibit neurobehavioral deficits and developmental delays in oligodendrocyte maturation and myelination, but the mechanisms which cause this delay are unknown. Inflammation may be an important etiological factor in IUGR and has been recognized as playi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The Th1 and Th2 subgroups of mice can secrete IL-2 and IL-4, respectively, and both IL-2 and IL-4 can promote the proliferation of T cells [43,44]. In addition, IL-4 can also promote the expression of B cells, enhance the antigen presentation ability of B cells, increase IgG1 and IgE levels, and make the responses of immune system to antigen stimulation [45,46]. Gong et al found that Bletilla baicalensis polysaccharides could significantly enhance the levels of IL-2 and IL-4 in immunosuppressed mice [47] which is similar with the effect of DZMP in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The Th1 and Th2 subgroups of mice can secrete IL-2 and IL-4, respectively, and both IL-2 and IL-4 can promote the proliferation of T cells [43,44]. In addition, IL-4 can also promote the expression of B cells, enhance the antigen presentation ability of B cells, increase IgG1 and IgE levels, and make the responses of immune system to antigen stimulation [45,46]. Gong et al found that Bletilla baicalensis polysaccharides could significantly enhance the levels of IL-2 and IL-4 in immunosuppressed mice [47] which is similar with the effect of DZMP in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…All in all these anti‐inflammatory cytokines contribute to a more favorable environment for neuronal and oligodendrocyte survival (Yang et al, 2009). Although protection by IL‐4 and IL‐10 is believed to be largely mediated through their role in dampening adverse inflammatory events, IL‐4 and IL‐10 can also directly target their respective receptors present on cells of the oligodendrocyte‐lineage (Molina‐Holgado, Vela, Arevalo‐Martin, & Guaza, 2001; Zanno et al, 2019). Intracellularly, IL‐10 activates the JAK/STAT and PI3k/Akt pathways (see Box 2; Zhou, Peng, Insolera, Fink, & Mata, 2009) while it is known IL‐4 targets PPARγ in OPCs, potentially through STAT6 (Zanno et al, 2019; Zhang et al, 2019).…”
Section: The Role Of Growth Factors and Cytokines In Oligodendrocyte mentioning
confidence: 99%
“…Specifically, oligodendrogenesis is instigated via IGF‐1 production by IL‐4‐conditioned microglia (Butovsky et al, 2006). The studies on direct effects of IL‐4 on OLs are conflicting as some studies find no direct effects of IL‐4 on cells of the oligodendrocyte‐lineage in vitro (Butovsky et al, 2006; Psachoulia et al, 2016), others report inhibition of differentiation of these cells (Zanno et al, 2019) or stimulation of OPC differentiation through transcription factor PPARγ (Zhang et al, 2019).…”
Section: The Role Of Growth Factors and Cytokines In Oligodendrocyte mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to investigations of white matter morphology, a key aspect of thinking about novel treatments has come from thinking about inflammation and the negative impact this may have on neurodevelopment. Investigators at the Children's Hospital of Philadelphia IDDRC present exciting work demonstrating that inflammation caused by Th2 cytokines during early brain development can be rescued with the application of IL-4 antibody treatment in the newborn rat [5]. This work highlights the importance of the immune system and impact on white matter development.…”
mentioning
confidence: 96%